Повноваження адвоката при здійсненні видачі (екстрадиції) особи - Монастирська, В. Ю.; Monastyrska, V. Yu. (Юридична наука. - 2019. - № 12 (102). - С. 370-379, 2019)
Наголошено, що Кримінальний процесуальний кодекс України регламентує участь адвоката (захисника), що здійснює захист особи, стосовно якої передбачається розгляд питання про видачу іноземній державі (екстрадицію). Запропоновано удосконалити нормативно-правову регламентацію участі адвоката (захисника) при вирішенні питання про видачу (екстрадицію) особи. Розглянуто повноваження адвоката при здійсненні міжнародного співробітництва під час кримінального провадження. Підкреслено, що права адвоката обумовлюються його діяльністю та достатньою мірою різноманітні, але всі вони забезпечують прийняття законного, справедливого рішення відносно осіб, які знаходяться у сфері дії правосуддя, враховуючи дотримання процесуальної форми національного кримінального процесу.

The Criminal Procedure Code of Ukraine regulates the participation of a lawyer (defense counsel) who protects a person in respect of whom consideration of extradition to a foreign state (extradition) is envisaged. It is necessary to improve the legal regulation of the participation of a lawyer (defender) in resolving the issue of extradition (extradition) of a person. It was found that the defense counsel involved in the extradition enjoys general rights, ie the rights of the suspect, accused, whose protection he exercises, except for procedural rights, which are exercised directly by the suspect, accused and cannot be entrusted to the defense counsel. In addition, it is proposed to make amendments to Chapter 44 of the CPC of Ukraine concerning the participation of a lawyer (defense counsel) during the extradition of a person to a foreign state: 1) participation of a lawyer in criminal proceedings for extradition to a state criminal liability or execution of a sentence is mandatory. The person has the right at the first request to communicate freely with a lawyer, confidentially and without limitation; 2) the lawyer has the right to get acquainted with the court decision on extradition of the person to the foreign state for implementation of criminal prosecution, serving of punishment, carrying out procedural actions; 3) the lawyer has the right to know about the circumstances that became the basis for consideration of the issue of extradition of a person to a foreign state and to get acquainted with the materials of the extradition inspection; 4) a lawyer has the right to participate in procedural actions related to the extradition of a person, to file a petition, to file complaints against the actions of officials conducting extradition proceedings, as well as to appeal against court decisions. We consider it expedient to make appropriate amendments to the CPC of Ukraine, to regulate the mandatory participation of a lawyer (defense counsel) in extradition proceedings. It is important for a lawyer to be involved in providing legal information, advice and clarification on legal issues, as well as drafting applications, complaints, procedural and other legal documents.

Отмечено, что Уголовный процессуальный кодекс Украины регламентирует участие адвоката (защитника), осуществляющего защиту лица, в отношении которого предполагается рассмотрение вопроса о выдаче иностранному государству (экстрадицию). Предложено усовершенствовать нормативно-правовую регламентацию участия адвоката (защитника) при решении вопроса о выдаче (экстрадиции) лица. Рассмотрены полномочия адвоката при осуществлении международного сотрудничества в ходе уголовного производства. Подчеркнуто, что права адвоката оговариваются его деятельностью и в достаточной степени разнообразны, но все они обеспечивают принятие законного, справедливого решения в отношении лиц, находящихся в сфере действия правосудия, учитывая соблюдение процессуальной формы национального уголовного процесса.
Power of attorney in exercise extradition (extradition) of a person
Монастирська, В. Ю. Повноваження адвоката при здійсненні видачі (екстрадиції) особи / Монастирська В. Ю. // Юридична наука. - 2019. - № 12 (102). - С. 370-379.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; criminal proceedings; уголовное производство; адвокат; lawyer; захисник; defender; защитник; екстрадиція; extradition; экстрадиция; кримінальне процесуальне законодавство; criminal procedural legislation; уголовное процессуальное законодательство; повноваження; powers; полномочия; міжнародне співробітництво; international cooperation; международное сотрудничество